1988
DOI: 10.1084/jem.168.1.375
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine inhibition of malaria is independent of host iron status.

Abstract: The mechanism whereby deferoxamine (DF) inhibits the growth of malaria parasites was studied in rats infected with Plasmodium berghei. Peak parasitemia was 32.6% (day 14) in untreated controls and 0.15% (day 7) in rats receiving 0.33 mg/g in 8 hourly DF injections, subcutaneously. DF inhibition of parasite growth was achieved without any reduction in transferrin saturation or hemoglobin synthesis and with only a partial (56%) depletion of hepatic iron stores. Dietary iron depletion resulted in anemia (hematocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
2
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 30 publications
1
54
2
1
Order By: Relevance
“…In contrast, little increase in these parameters has been found in human [16] and rat [7] malaria. Hepatic non-heme iron was found in the present study to be markedly elevated in Theileria-infected calves, whereas there is no significant increase in hepatic non-heme iron in malaria-infected rats with anemia [7].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little increase in these parameters has been found in human [16] and rat [7] malaria. Hepatic non-heme iron was found in the present study to be markedly elevated in Theileria-infected calves, whereas there is no significant increase in hepatic non-heme iron in malaria-infected rats with anemia [7].…”
Section: Discussionmentioning
confidence: 99%
“…The source ofthis iron for the malaria parasite is unclear. Some evidence suggests that it derives from host iron transferrin (28)(29)(30) and other evidence suggests that it derives from host erythrocyte hemoglobin (31,32). Whatever the source of iron, its intracellular mobilization is likely dependent upon acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The information available indicates that DFO acts without affecting serum (4,10) or normal red cell iron pools (3,10), that it gains a restricted access to infected cells ( 11 ), and that its antimalarial action is manifested only in the advanced stages of parasite development and only after prolonged exposure of cells to drug (3,12). All this evidence implies that DFO gains a slow and limited access to the mature stages of erythrocytic parasites where it exerts cytotoxic action on still unidentified parasite targets.…”
mentioning
confidence: 99%
“…Recently it was shown that DFO congeners display effective antimalarial activity both in vitro (2)(3)(4)(5) and in vivo (4,(6)(7)(8)(9), but as with many other drugs, their mode of action has remained elusive (1). The information available indicates that DFO acts without affecting serum (4,10) or normal red cell iron pools (3,10), that it gains a restricted access to infected cells ( 11 ), and that its antimalarial action is manifested only in the advanced stages of parasite development and only after prolonged exposure of cells to drug (3,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation